1993
DOI: 10.1002/ajmg.1320470211
|View full text |Cite
|
Sign up to set email alerts
|

Multiple meningiomas in a patient with constitutional ring chromosome 22

Abstract: We report on a patient with multiple congenital anomalies and ring chromosome 22 who died at age 16 years of bronchopneumonia. Autopsy documented multiple psammomatous meningiomas of the spinal dura and tentorium. Tumor tissue for cytogenetic analysis was not available. Although abnormalities of chromosome 22 in tumor tissue have been reported, to our knowledge, this is only the third report of a constitutional chromosome 22 abnormality associated with the development of meningiomas. Thus, a constitutional chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…[8][9][10][11][12] Kehrer-Sawatzki et al 8 suggested dividing r (22) patients into three groups: patients with NF2, those without NF2 but with multiple meningiomatosis, and those without features of either disease. Each of the classical r (22) patients in the present study have NF2.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Kehrer-Sawatzki et al 8 suggested dividing r (22) patients into three groups: patients with NF2, those without NF2 but with multiple meningiomatosis, and those without features of either disease. Each of the classical r (22) patients in the present study have NF2.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a highly proliferating melanocytic congenital naevus with somatic mosaicism of chromosome 7 was found in a male child with a constitutional ring chromosome 7 (Mehraein et al, 2004). A close association between constitutional rings of chromosome 22 and meningiomas (Arinami et al, 1986;Petrella et al, 1993) or neurofibromatosis 1 or 2 (Duncan et al, 1987;Kehrer-Sawatzki et al, 1997;Tsilchorozidou et al, 2004) is well documented. In addition, an atypical teratoid/rhabdoid brain tumor was found in a girl with r(22) (Rubio, 1997).…”
Section: Constitutional Rings and Neoplasiamentioning
confidence: 92%
“…In contrast, the presence of a large number of cells with loss of the r (22), resulting in loss of the NF2 gene and other tumour suppressor genes on chromosome 22, could increase the risk of developing neurofibromatosis [23][24][25][26] and also tumours of the nervous system. [27][28][29][30] The 22q13 deletions are most often paternal in origin The expression of the phenotype was not affected by parental origin of the deleted chromosome in either the 22q13 deletion syndrome or the r(22) syndrome. Nevertheless, we showed a strong excess of paternal origin of the 22q13 deletions for all classes of rearrangement.…”
Section: Is There Any Difference Between the R(22) And The Del(22)(q1mentioning
confidence: 99%